Traditional dairy production among smallholders in Malaysia. - Syed Salim, Syed Jalaludin; Khoo, K. H. (1980)
A study on farming practices was undertaken on 10 dairy cattle farms in the State of Selangor. The number of cattle on each farm ranged from 14 to 60. The data was collected in a questionnaire over a 4 week period. The basic methods of husbandry were practised involving mainly free grazing and minimum concentrate feeding. The average milk yield was 2.72 litres per day. The nutritional, breeding and management practices were evaluated and the constraints of the farming system were highlighted and discussed.